Masculinization of Betta Fish (Betta splendens) Through Soaking Larvae Using Goat Testicular Flour - Wisnu Kusuma, Pungky Slamet; Sholeh, Ismail (Agrikan Jurnal Agribisnis Perikanan, 2022)
Male betta fish is known as an ornamental fish that has varied tail colors and shapes, these advantages are what make the price more expensive in the market but to get a population of male betta fish obtained from natural spawning is very low. One of the efforts to increase the number of male betta fish populations is carried out masculinization method through the use of goat testicular flour solution. This study aims to determine the effect of the length of soaking of betta fish larvae in a solution of goat testicular flour on the success of sex changes of male betta fish. The experimental study used a Complete Randomized Design (RAL) with 4 treatments and 5 tests. The treatment in this study was that the larvae of betta fish aged 4 days were soaked in a solution of goat testicular flour at different doses. Control, P1 (24-hour soaking dose 60 ppm), P2 (36-hour soaking dose 70 ppm), and P3 (48-hour soaking dose 80 ppm). An observed variable percentage of male betta fish. Data analysis using ANOVA, if there is a difference, followed by the Tukey Test. Sexes are distinguished by observations morphologically. The results showed that the duration of soaking 24 hours at a dose of 60 ppm resulted in the highest percentage of male betta fish 73.37% with a survival rate of 78%.